Neutrophils in tissue injury and repair - Wang, Jing (Cell and tissue research, 2018)
As one of the first defenders of innate immune response, neutrophils make a rapid and robust response against infection or harmful agents. While traditionally regarded as suicidal killers that cause collateral tissue damage, recent findings on neutrophil extracellular trap formation, heterogeneity and plasticity and novel reparative functions have expanded our understanding of their diverse roles in health and disease. This review summarizes our current understanding of neutrophil-associated tissue injury, highlighting the emerging roles of neutrophil extracellular traps. This review will also focus on scrutinizing the roles of neutrophils in tissue repair and regeneration and will examine data on unexpected aspects of involvement of neutrophils in regulating normal tissue homeostasis.